A novel, de novo intronic variant in POGZ causes White–Sutton syndrome. Issue 7 (9th April 2022) - Merriweather, Ashanta; Murdock, David R.; Rosenfeld, Jill A.; Dai, Hongzheng; Ketkar, Shamika; Emrick, Lisa; Nicholas, Sarah; Lewis, Richard A.; ,; Bacino, Carlos A.; Scott, Daryl A.; Lee, Brendan; et al.
Abstract: White–Sutton syndrome (WHSUS), which is caused by heterozygous pathogenic variants in POGZ, is characterized by a spectrum of intellectual disabilities and global developmental delay with or without features of autism spectrum disorder. Additional features may include hypotonia, behavioral abnormalities, ophthalmic abnormalities, hearing loss, sleep apnea, microcephaly, dysmorphic facial features, and rarely, congenital diaphragmatic hernia (CDH). We present a 6‐year‐old female with features of WHSUS, including CDH, but with nondiagnostic clinical trio exome sequencing. Exome sequencing reanalysis revealed a heterozygous, de novo, intronic variant in POGZ (NM_015100.3:c.2546‐20T>A). RNA sequencing revealed that this intronic variant leads to skipping of exon 18. This exon skipping event results in a frameshift with a predicted premature stop codon in the last exon and escape from nonsense‐mediated mRNA decay (NMD). To our knowledge, this case is the first case of WHSUS caused by a de novo, intronic variant that is not near a canonical splice site within POGZ . These findings emphasize the limitations of standard clinical exome filtering algorithms and the importance of research reanalysis of exome data together with RNA sequencing to confirm a suspected diagnosis of WHSUS. As the sixth reported case of CDH with heterozygous pathogenic variants in POGZ and features consistent with WHSUS, this report supports the conclusion that WHSUS should be considered in the differential diagnosis for patients with syndromic CDH.